Принцип когнитивной экономии как важный фактор в передаче информации - Rasulov , Zubaydullo (Центр Научных Публикаций (buxdu.uz), 2023)
The article examines the role of the principle of economy in the research of the systemic functioning of language, the history of the formation of a scientific theoretical description of this principle, theoret ical ideas about the role of the principle of economy in the evolution of language, attempts to simplify the content in order to facilitate language activity and, accordingly, contradictory theories of the formation of the law of economy of speech. It is proved that the categorical ordering of reality does not arise as a result of some random or free choice, but under the influence of certain types of psychological principles.